Exploring Discrimination in Education: A Phenomenological Study of the Niqab Restrictions in Higher Education - Annas Azizil Alim; Mohammad Zakki Azani (Yayasan Letiges Konsultan Sosial, 2024)
This research aims to explain the phenomenon of discrimination against female students who wear the niqab in higher education. This research was conducted because there is a phenomenon of discrimination in education in the form of a ban on wearing the niqab in several universities. This research uses a phenomenological approach with descriptive and qualitative methods. This research was conducted at a private Islamic college in Surakarta. The informants in this research were 16 female students who wore the niqab in the university environment. The data collection technique used was structured interviews. After collecting the data, the researcher conducted a data analysis process, including data reduction, data presentation and concluding. According to the research's findings, discrimination in academic and extracurricular activities is a problem faced by students in higher education. These obstacles impact achieving academic grades that are not optimal and limitations in socialising. Thus, it is necessary to instil more intensive Islamic knowledge in universities to reduce socio-religious problems.